Peri-operative monitoring of general anaesthesia in buffaloes undergoing diaphragmatic herniorrhaphy in relation to pleural integrity and survivability - SINGH, TARUNDEEP; SANGWAN, VANDANA; SHARMA, KARTIK; KUMAR, ASHWANI; VERMA, ABHISHEK; SINGH, NAVDEEP; JENA, BISWADEEP; KHOSA, JASMEET SINGH (The Indian Journal of Animal Sciences, 2023)
The present study aimed to monitor the general anaesthesia (midazolam-propofol and isoflurane) in 31 buffaloes undergoing diaphragmatic herniorrhaphy in relation to pleural integrity and survivability. Various herniorrhaphy and peri-operative anaesthetic parameters of heart rate, respiration rate, SpO2, apnea, corneal reflex, lacrimation, salivation, regurgitation and position of eyeball were recorded. The data was compared between the survivor (26/31=83.87%, Group 1) and the non-survivor group (Group 2) and between the buffaloes with intact pleura during herniorrhaphy (21/31= 67.75%, Group 3) and those with ruptured pleura (Group 4). Majority of the buffaloes (80%) in Group 2 had ruptured pleura during herniorrhaphy, while in Group 1, 76.92% had intact pleura. The corneal reflex was considered the most reliable manual parameter to assess the survival status of the buffalo in ventro-dorsal position and its absence was considered alarming. The heart rate was significantly higher in Group 2 in comparison to Group 1 after breaking of hernia ring adhesions. The SpO2 of Group 4 was always lower than in Group 3 and at the time of rupture of pleura it was significantly low but improved with suction and intermittent positive pressure ventilation in Group 1 buffaloes. The study recommended perioperative monitoring of eye reflexes, heart rate, respiration rate, and SpO2 during diaphragmatic herniorrhaphy in buffaloes to take necessary precautions for the timely removal of free air from the pleural space. The integrity of the pleura plays an important role in the survival of buffaloes undergoing herniorrhaphy.